Prescription Rates, Polypharmacy and Prescriber Variability in Swiss General Practice—A Cross-Sectional Database Study - Rachamin, Yael; Jäger, Levy; Meier, Rahel; Grischott, Thomas; Senn, Oliver; Burgstaller, Jakob M.; Markun, Stefan (Frontiers in Pharmacology, 2022)
Purpose: The frequency of medication prescribing and polypharmacy has increased in recent years in different settings, including Swiss general practice. We aimed to describe patient age- and sex-specific prescription rates of polypharmacy and of the most frequent medication classes, and to explore practitioner variability in prescribing. Methods: Retrospective cross-sectional study based on anonymized electronic medical records data of 111 811 adult patients presenting to 116 Swiss general practitioners in 2019. We used mixed-effects regression analyses to assess the association of patient age and sex with polypharmacy (≥5 medications) and with the prescription of specific medication classes (2nd level of the Anatomical Therapeutic Chemical Classification System). Practitioner variability was quantified in terms of the random effects distribution. Results: The prevalence of polypharmacy increased with age from 6.4% among patients aged 18-40 years to 19.7% (age 41-64 years), 45.3% (age 65-80 years), and 64.6% (age 81-92 years), and was higher in women than in men, particularly at younger ages. The most frequently prescribed medication classes were “antiinflammatory and antirheumatic products” (21.6% of patients), “agents acting on the renin-angiotensin system” (19.9%), “analgesics” (18.7%), and “drugs for acid related disorders” (18.3%). Men were more often prescribed agents targeting the cardiovascular system, whereas most other medications were more often prescribed to women. The highest practitioner variability was observed for “vitamins”, “antiinflammatory and antirheumatic products”, and “mineral supplements”. Conclusion: Based on practitioner variability, prevalence, and risk potential, antiinflammatory drugs and polypharmacy in older patients appear to be the most pressing issues in current drug prescribing routines.